Exploring learners' perception on improving their willingness to communicate in English through experiential learning among undergraduate students - Abd Rahman, Siti Nadhirah; Abd Samad, Arshad; Abu Bakar, Norlida (Horizon Research Publishing, 2020)
The purpose of this study is to explore the expectations and goals of students when participating in language activities, and how they perceive their willingness to communicate. The language activities involved in this study are LAX activities which are compulsory for all undergraduate students within this institution. Throughout the LAX activities, the students go through a form of experiential learning where they will have to complete a task, reflect on their work, and apply what they have learned. The students are interviewed regarding their expectations and goals prior to doing the language activities and their willingness to communicate during and after having done the activities. The findings show that students did set up positive goals before participating in the language activities, but they had negative expectations of the experience. It was also found that the students perceive an improvement in their willingness to communicate after participating in the activities. In the future, experiential learning could be implemented in language learning for positive outcomes, and more studies can be done on the topic to improve second language learning.